Effect of material properties on emotion: a virtual reality study - Bertheaux, Cyril; Zimmermann, Eliott; Gazel, Mathis; Delanoy, Johanna; Raimbaud, Pierre; Lavoué, Guillaume (Frontiers in Human Neuroscience, 2024)
Designers know that part of the appreciation of a product comes from the properties of its materials. These materials define the object's appearance and produce emotional reactions that can influence the act of purchase. Although known and observed as important, the affective level of a material remains difficult to assess. While many studies have been conducted regarding material colors, here we focus on two material properties that drive how light is reflected by the object: its metalness and smoothness. In this context, this work aims to study the influence of these properties on the induced emotional response. We conducted a perceptual user study in virtual reality, allowing participants to visualize and manipulate a neutral objecta mug. We generated 16 material effects by varying it metalness and smoothness characteristics. The emotional reactions produced by the 16 mugs were evaluated on a panel of 28 people using James Russel's circumplex model, for an emotional measurement through two dimensions: arousal (from low to high) and valence (from negative to positive). This scale, used here through VR users' declarative statements allowed us to order their emotional preferences between all the virtual mugs. Statistical results show significant positive effects of both metalness and smoothness on arousal and valence. Using image processing features, we show that this positive effect is linked to the increasing strength (i.e., sharpness and contrast) of the specular reflections induced by these material properties. The present work is the first to establish this strong relationship between specular reflections induced by material properties and aroused emotions.